Preparing a Bioactive (Chitosan/Sodium Hyaluronate)/SrHA Coating on Mg–Zn–Ca Alloy for Orthopedic Implant Applications - Feng, Yashan; Chang, Lei; Zhu, Shijie; Yang, Yongxin; Wei, Baoli; Lv, Meng; Wang, Jun; Guan, Shaokang (Frontiers in Materials, 2022)
The uncontrollable rapid degradation rate of the Mg alloy substrate limited their clinical application. And implant-associated infections have been reported to be the main reason for the secondary surgery of orthopedic implantation. The aim of this study is to produce a multi-functional coating on magnesium-based alloys that has improved corrosion resistance, bioactivity and antibacterial properties through the preparation of polyelectrolytic multilayers (PEMs) consisting of chitosan (CS) and sodium hyaluronate (HA) on silane-modified strontium-substituted hydroxyapatite (hereafter, referred to as Bil(SH+CS)/SrHA). The multi-functional coatings were characterised by scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS). The results showed the polyelectrolyte complex SH/CS layer to be uniformly and tightly attached on to the surface of silane-treated SrHA. At the same time, a potentiodynamic polarisation test and hydrogen evolution test showed the Bil(SH+CS)/SrHA coatings to exhibit superior corrosion resistance in comparison to bulk Mg-based alloys. The results of the cell-surface interactions revealed Bil(SH+CS)/SrHA coatings to be in favor of cell initial adhesion and more beneficial to the proliferation and growth of cells with the processing of co-culture. In addition, antibacterial tests demonstrated the strong bactericidal effect of Bil(SH+CS)/SrHA coatings against both Escherichia coli (E.coli) and Staphylococcus (S.aureus), suggesting that Bil(SH+CS)/SrHA coatings can successfully achieve multi-functionality with enhanced corrosion resistance, biocompatibility and antibacterial properties.